Mechanical and microstructure performance and global warming potential of blended concrete containing rice husk ash and silica fume. (5th September 2022) - Nasir Amin, Muhammad; Ur Rehman, Khalil; Shahzada, Khan; Khan, Kaffayatullah; Wahab, Nauman; Abdulalim Alabdullah, Anas
Highlights: RHA and SF are being used as partial replacements for cement to produce high-performance and sustainable concrete. 20% addition of RHA (RHA20) increased concrete's tensile and compressive strength. High volume replacement of cement as 33% RHA with 7% SF (RHA33SF7) produced adequate strength. Reduction in portlandite phase and densification of micro and pore structures observed in RHA20 and RHA33SF7. Abstract: The influence of cement replacement by rice husk ash (RHA) and silica fume (SF) is explored in this study. Several microstructural and mechanical properties of the control and different binary and ternary blends of concrete with various amounts of cement, RHA and SF were determined. The binary mix with 20% RHA (RHA20) as well as a ternary mix having 33% RHA along with 7% SF (RHA33SF7) presented highest strengths which is further confirmed from their lowest water absorption and apparent porosity values. The SEM-EDS analysis revealed the formation of dense and compact microstructure in RHA20 and RHA33SF7 probably due to the calcium hydroxide (CH) and highly dense calcium silicate hydrate (C-S-H) phases. Moreover, an increase in the Brunauer-Emmett-Teller surface area along with a reduction in intruded volume, as determined by the N2 adsorption isotherm analysis, proved the densified pore structure of these mixes. The results of the Fourier transform infrared (FTIR) spectroscopy showed a significant shift in the band from 955 to 977 cm −1 due to addition of RHA and SF that causes large amounts of C-S-H gels to form in these mixes. Moreover, both FTIR and thermogravimetric analysis analyses also showed significant reduction of their portlandite phase. In addition to enhanced micro-structural and mechanical performances, a relatively lower CO2 -eq (equivalent to kg CO2 ) per MPa for RHA20 and RHA33SF7 indicates the significant positive impact of using higher amounts of regionally available supplementary cementitious materials in producing green concretes due to their reduced Global Warming Potential. The current findings demonstrated both RHA and SF to be used in concrete industry as a possible revenue source for developing sustainable concretes with high performance.